Ordinance No. 1052, §§ 1-2, 5, & 8-9, Vancouver City Council (1920) (Vancouver, Washington). - (:unkn) unknown (My University, 1920)
It shall be unlawful for any person to sell, give away, purchase or receive any pistol, revolver, derringer, bowie knife, dirk, or other weapon of like character which can be concealed on the person without securing and requiring the proper license to do as hereinafter set forth. No person shall sell, give away or deal in the weapons herein specified without first obtaining from the Chief of Police of Vancouver, Washington, a license so to do,
Keywords: LICENSE - DEALERS; TRANSFER